Growth in Children After Kidney Transplantation - Saygılı, Seha Kamil; Kezer, Seçil; Karabağ Yılmaz, Esra; Gülmez, Rüveyda; Demirgan, Ebru Burcu; Ağbaş, Ayse; Eliçevik, Mehmet; Canpolat, Nur (Cerrahpaşa Medical Journal, 2023)
Objective: Kidney transplantation can improve linear growth in pediatric recipients but may not ensure attainment of the target adult height. The aim of this study is to determine the prevalence of growth failure in pediatric kidney transplantation recipients and to investigate the factors that influence growth. Methods: This single-center retrospective study included 62 kidney transplantation recipients (37 males) transplanted before 18 years of age. Patients’ medical records were retrospectively reviewed for annual posttransplant anthropometric measurements. Target height was calculated based on midparental height. The standard deviation score of height was calculated for baseline (at transplantation), final (at study time), and target heights. Results: The median age at transplantation was 11.9 (8.8-14.8) years, and the median follow-up time after transplantation was 5.9 (3.2-7.2) years. Forty-seven children (76%) had growth failure (standard deviation score of height < –1.88) at baseline. After transplantation, a significant increase in the standard deviation score of height was observed between baseline and final (P < .001); however, the final standard deviation score of height was significantly lower than the target standard deviation score of height (P < .001), and 38 patients (61%) still had growth failure at final examination. Twenty-seven patients (43.5%) achieved their target SD score of height. Children transplanted over 12 years had lower growth velocity (cm/year) than those transplanted at 2-5 years and 5-12 years (P < .05). A high final standard deviation score of height was independently associated with lower transplant age, higher baseline standard deviation score of height, and lower cumulative steroid dose (P < .05 for all). Conclusion: Kidney transplantation improves linear growth in pediatric recipients, but growth failure is still common after transplantation, and most patients are unfortunately far from their target height. Cite this article as: Saygılı SK, Kezer S, Karabağ Yılmaz E, et al. Growth in children after kidney transplantation. Cerrahpaşa Med J. 2023;47(2):182-186.